2022
DOI: 10.21037/qims-21-113
|View full text |Cite
|
Sign up to set email alerts
|

Is treated hypopituitarism associated with increased left ventricular strains?—detailed analysis from the three-dimensional speckle-tracking echocardiographic MAGYAR-Path Study

Abstract: Reduced secretion of one or more of the hormones normally produced by the pituitary gland is called hypopituitarism, which is a rare and frequently underdiagnosed condition. Hypopituitarism can be present at birth called congenital or may develop due to acquired causes like tumor, infection, infiltration, vascular or other causes. Symptoms of hypopituitarism are highly dependent on which hormones are insufficient. The present prospective study was designed to test whether treated hypopituitarism is associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
4
1
Order By: Relevance
“…Mihaila et al presented decreased 2DSTE-derived longitudinal (LS) and circumferential strains in the presence of GH deficiency, which was accompanied with impaired LV basal rotation and twist (29). In contrast, increased 3DSTE-derived LS and area strain could be detected in our group of patients with treated hypopituitarism in a recent study, in which most cases had GH deficiency (19). In the present study, reduced LV twist was associated with impaired LV apical rotation and preserved LV basal rotation in patients with normally directed LV rotational mechanics, in which abnormalities were present regardless of the type of hypopituitarism (congenital vs. acquired).…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…Mihaila et al presented decreased 2DSTE-derived longitudinal (LS) and circumferential strains in the presence of GH deficiency, which was accompanied with impaired LV basal rotation and twist (29). In contrast, increased 3DSTE-derived LS and area strain could be detected in our group of patients with treated hypopituitarism in a recent study, in which most cases had GH deficiency (19). In the present study, reduced LV twist was associated with impaired LV apical rotation and preserved LV basal rotation in patients with normally directed LV rotational mechanics, in which abnormalities were present regardless of the type of hypopituitarism (congenital vs. acquired).…”
Section: Discussioncontrasting
confidence: 48%
“…Early detection of changes in LV volumetric and functional abnormalities could help in selecting patients with increased risk. In recent studies, diagnostic and prognostic impact of LV deformation have been demonstrated in several disorders (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). LV has a special 3D movement respecting the cardiac cycle as well due to its special helical 3D structure.…”
Section: Discussionmentioning
confidence: 99%
“…❖ Moreover, volumetric and functional features of other cardiac chambers were also not examined ( 18 , 19 ).…”
Section: Discussionmentioning
confidence: 99%
“… Direct comparison of 2D echocardiography-and 3DSTE-derived RA parameters was not aimed to be performed.  Moreover, volumetric and functional features of other cardiac chambers were also not examined (18,19).  Only 3DSTE-derived RA volumes were measured.…”
Section: Limitation Sectionmentioning
confidence: 99%
“…❖ Known technical limitations of 3DSTE are reduced spatial resolution and lower frame rate as compared to 2DE ( 4 - 7 , 19 , 20 ).…”
Section: Discussionmentioning
confidence: 99%